Emergent Computation A Festschrift for Selim G. Akl - Adamatzky, Andrew; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is dedicated to Professor Selim G. Akl to honour his groundbreaking research achievements in computer science over four decades. The book is an intellectually stimulating excursion into emergent computing paradigms, architectures and implementations. World top experts in computer science, engineering and mathematics overview exciting and intriguing topics of musical rhythms generation algorithms, analyse the computational power of random walks, dispelling a myth of computational universality, computability and complexity at the microscopic level of synchronous computation, descriptional complexity of error detection, quantum cryptography, context-free parallel communicating grammar systems, fault tolerance of hypercubes, finite automata theory of bulk-synchronous parallel computing, dealing with silent data corruptions in high-performance computing, parallel sorting on graphics processing units, mining for functional dependencies in relational databases, cellular automataoptimisation of wireless sensors networks, connectivity preserving network transformers, constrained resource networks, vague computing, parallel evolutionary optimisation, emergent behaviour in multi-agent systems, vehicular clouds, epigenetic drug discovery, dimensionality reduction for intrusion detection systems, physical maze solvers, computer chess, parallel algorithms to string alignment, detection of community structure. The book is a unique combination of vibrant essays which inspires scientists and engineers to exploit natural phenomena in designs of computing architectures of the future.
Simple Deterministic Algorithms for Generating "Good" Musical Rhythms.- A Hierarchy for BPP log based on Counting Calls to an Oracle.- On Computable Numbers, Nonuniversality, and the Genuine Power of Parallelism -- On the Microscopic View of Time and Messages -- Descriptional Complexity of Error Detection.-A Less Known Side of Quantum Cryptography -- Emergence in Context-Free Parallel Communicating Grammar Systems: What Does and Does Not Make a Grammar System More Expressive than Its Parts.-Structural Properties of the Generalized Exchanged Hypercubes.- Enumerated BSP Automata -- Coping with Silent Errors in HPC Applications.- Parallel Sorting For GPUs.- Mining for Functional Dependencies Using Shared Radix Trees in Many-Core Multi-Threaded Systems.- Cellular Automata and Wireless Sensor Networks.- Connectivity Preserving Network Transformers.- Operating Secure Mobile Healthcare Services over Constrained Resource Networks.- On Vague Computers.- Parallel evolutionary Optimization of Natural Convection Problem.- Theory and Practice of Discrete Interacting Agents Models.-Vehicular Clouds: Ubiquitous Computing on Wheels.- Computational Approaches to Epigenetic Drug Discovery.-Dimensionality Reduction for Intrusion Detection Systems in Multi-data Streams- a Review and Proposal of Unsupervised Feature Selection Scheme -- Physical Maze Solvers. All Twelve Prototypes Implement 1961 Lee algorithm -- Computer Chess Endgame Play with Pawns: Then and Now.- Community Detection Using Synthetic Coordinates and Flow Propagation.
Keywords: Computational intelligence; Artificial intelligence; Algorithms; Dynamics; Nonlinear theories; Computational Intelligence; Artificial Intelligence; Algorithms; Applied Dynamical Systems